Education for Citizenship in Europe European Policies, National Adaptations and Young People's Attitudes - Keating, Avril; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book examines the evolving relationship between the nation-state, citizenship and the education of citizens, exploring the impact European integration had on national policies towards educating its citizens and citizenship.
Keywords: Science; Science; Science, general